2005
DOI: 10.1128/jvi.79.10.6005-6022.2005
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Human Glioblastoma Cells: Comparison of Nine Viruses with Oncolytic Potential

Abstract: Brain tumors classified as glioblastomas have proven refractory to treatment and generally result in death within a year of diagnosis. We used seven in vitro tests and one in vivo trial to compare the efficacy of nine different viruses for targeting human glioblastoma. Green fluorescent protein (GFP)-expressing vesicular stomatitis (VSV), Sindbis virus, pseudorabies virus (PRV), adeno-associated virus (AAV), and minute virus of mice i-strain (MVMi) and MVMp all infected glioblastoma cells. Mouse and human cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(126 citation statements)
references
References 55 publications
(74 reference statements)
6
119
0
1
Order By: Relevance
“…Thus, MV could be a useful therapeutic agent in at least a subset of rhabdoid tumor. Cui et al (12) Despite a rapidly increasing number of studies examining the utility of oncolytic viruses against many cancers, there have been few comparisons of the efficacy or toxicity of multiple oncolytic viruses in a single model (19,43). Here, we have directly compared the oncolytic efficacy of MV and VSV…”
Section: Discussionmentioning
confidence: 99%
“…Thus, MV could be a useful therapeutic agent in at least a subset of rhabdoid tumor. Cui et al (12) Despite a rapidly increasing number of studies examining the utility of oncolytic viruses against many cancers, there have been few comparisons of the efficacy or toxicity of multiple oncolytic viruses in a single model (19,43). Here, we have directly compared the oncolytic efficacy of MV and VSV…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is likely that the type I IFN response, perhaps in concert with other components of the innate immune response, is one of the major hurdles against successful virotherapy. 30 In nude mice, also virus-specific IgM plays an important role in controlling the infection, and although antibodies alone are unable to clear the virus from the CNS, they may remove it from the subcutaneous tumors. 21,22 It has been shown that the vasculature in many solid tumors is leaky for serum protein components, including immunoglobulins.…”
Section: Discussionmentioning
confidence: 99%
“…The first report about cytotoxicity of a parvovirus against transformed neural cells was on the MVMp and MVMi infection of rat C6 glioma and several human glioblastoma and astrocytoma cells (Rubio et al 2001). The MVM infections of human cells were cytotoxic but poorly productive, as found some years afterwards by an independent study (Wollmann et al 2005). Although a parallel study with the MVM and H-1 viruses has not being carefully addressed, several subsequent reports suggested that H-1 is a more powerful oncolytic agent against human glioblastoma, regarding the levels of both cytotoxicity and virus yield in culture (Herrero et al 2004;Di Piazza et al 2007).…”
Section: Parvoviruses As Oncolytic Agentsmentioning
confidence: 92%